Linkage analysis and residual heterozygotes derived near isogenic lines reveals a novel protein quantitative trait loci from a Glycine soja accession - Yang, Yia; La, Thang C.; Gillman, Jason D.; Lyu, Zhen; Joshi, Trupti; Usovsky, Mariola; Song, Qijian; Scaboo, Andrew (Frontiers in Plant Science, 2022)
Modern soybean [Glycine max (L.) Merr] cultivars have low overall genetic variation due to repeated bottleneck events that arose during domestication and from selection strategies typical of many soybean breeding programs. In both public and private soybean breeding programs, the introgression of wild soybean (Glycine soja Siebold & Zucc.) alleles is a viable option to increase genetic diversity and identify new sources for traits of value. The objectives of our study were to examine the genetic architecture responsible for seed protein and oil using a recombinant inbred line (RIL) population derived from hybridizing a G. max line (‘Osage’) with a G. soja accession (PI 593983). Linkage mapping identified a total of 7 significant quantitative trait loci on chromosomes 14 and 20 for seed protein and on chromosome 8 for seed oil with LOD scores ranging from 5.3-31.7 for seed protein content and 9.8-25.9 for seed oil content. We analyzed 3,015 single F4:9 soybean plants to develop two residual heterozygotes derived near isogenic lines (RHD-NIL) populations by targeting nine SNP markers from genotype-by-sequencing which corresponded to two novel QTL derived from G. soja: one for a novel seed oil QTL on chromosome 8 and another for a novel protein QTL on chromosome 14. Single marker analysis and linkage analysis using 50 RHD-NILs validated the chromosome 14 protein QTL and whole genome sequencing of RHD-NILs allowed us to reduce the QTL interval from ~16.5 Mbp to ~4.6 Mbp. We identified two genomic regions based on recombination events which had significant increases of 0.65% and 0.72% in seed protein content without significant decrease in seed oil content. A new Kompetitive allele specific polymerase chain reaction (KASP) assay which will be useful for introgression of this trait into modern elite G. max cultivars was developed in one region. Within the significantly associated genomic regions, a total of eight genes are considered as candidate genes, based on the presence of gene annotations associated with protein or amino acid metabolism/movement. Our results provide better insight of utilizing wild soybean as a source of genetic diversity for soybean cultivar improvement utilizing native traits.